2020
DOI: 10.3389/fpsyg.2020.01385
|View full text |Cite
|
Sign up to set email alerts
|

When in Doubt, Follow the Crowd? Responsiveness to Social Proof Nudges in the Absence of Clear Preferences

Abstract: Nudges have gained popularity as a behavioral change tool that aims to facilitate the selection of the sensible choice option by altering the way choice options are presented. Although nudges are designed to facilitate these choices without interfering with people's prior preferences, both the relation between individuals' prior preferences and nudge effectiveness, as well as the notion that nudges 'facilitate' decision-making have received little empirical scrutiny. Two studies examine the hypothesis that a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 64 publications
0
24
1
Order By: Relevance
“…2,3 The observed substantial increase in acceptance during the survey period should be interpreted cautiously because of the reduced sample size over time and because survey latecomers may not be representative. Still, intervening events may have signaled that receiving a vaccine is safe, normative, 4 historic, and an indication of HCWs' important role in the pandemic response. The trend of increased intention to receive a vaccine as the EUA processes unfolded and the greater number of employees who actually received a vaccine compared with respondents who intended to do so suggest that the highly visible nature of the actual processes may have reassured many respondents.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The observed substantial increase in acceptance during the survey period should be interpreted cautiously because of the reduced sample size over time and because survey latecomers may not be representative. Still, intervening events may have signaled that receiving a vaccine is safe, normative, 4 historic, and an indication of HCWs' important role in the pandemic response. The trend of increased intention to receive a vaccine as the EUA processes unfolded and the greater number of employees who actually received a vaccine compared with respondents who intended to do so suggest that the highly visible nature of the actual processes may have reassured many respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Although caution is warranted in interpreting our observed day-by-day increase in vaccine acceptance as representative of our sample population, these events could have helped associate COVID-19 vaccines with several sentiments that should increase intention to receive a vaccination. These include: the sense the receiving a COVID-19 vaccine is normative among influential people and/or HCWs (Cialdini, 2007; Goldstein et al, 2008; Salmon et al, 2014; Venema et al, 2020); that, perhaps unlike some other pandemic behaviors, vaccination is bipartisan; that in receiving a COVID-19 vaccine, especially in the first wave, one participates in an historic moment; and that early vaccination is a reflection of the importance of one’s heroic role on the front lines of the pandemic response, such that being deprioritized for vaccination is, in the words of one healthcare worker, “insulting” (Bernstein et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This nudge was also made redundant in those with a strong health goal by a pre-existing (nudge-congruent) preference for a small soft drink (Venema et al, 2019). In fact, nudges exert the strongest influence when individuals are uncertain or ambivalent about their choices and in need of choice support, as in the case of conflicting preferences (Venema et al, 2020a). Given the ethical debate on nudges potentially violating autonomous choice, these findings provide initial evidence that nudging may support action on 'medium-size' preferences (autonomy as self-constitution) and provide assistance in cases of decision uncertainty (autonomy as agency).…”
Section: Ease Of Accomplishing Behavioural Changementioning
confidence: 99%
“…Hence, in this paper, we demonstrate the inefficacy of this isolationist approach by drawing on research from the Welfare Improvement through Nudging Knowledge (WINK) project, which examines nudging from the perspective of three core disciplines: ethics, public administration and psychology. Empirical studies from each of these disciplinary perspectives in our project have recently been published (e.g., Feitsma, 2018Feitsma, , 2019Vugts et al, 2018;Venema et al, 2019Venema et al, , 2020aVenema et al, , 2020b. Here, we focus on a synthesized review of the results from these studies, supplemented with literature discussing the issues that we identified as common themes in our multidisciplinary approach.…”
Section: Introductionmentioning
confidence: 99%